2021
DOI: 10.1177/2325967120985153
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Clinical and Radiologic Outcomes Between an Anatomic Tunnel and a Low Tibial Tunnel in Remnant-Preserving Posterior Cruciate Ligament Reconstruction

Abstract: Background: There is currently no consensus on the optimal placement of the tibial tunnel for remnant-preserving posterior cruciate ligament (PCL) reconstruction. Purpose/Hypothesis: The purpose of this study was to compare the clinical and radiologic outcomes of remnant-preserving PCL reconstruction using anatomic versus low tibial tunnels. We hypothesized that the outcomes of low tibial tunnel placement would be superior to those of anatomic tibial tunnel placement at the 2-year follow-up after remnant-prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…With the development of arthroscopic techniques, PCL reconstruction is becoming a common treatment strategy for PCL injuries. Precise anatomical positioning of the graft tunnel is essential for obtaining good PCL reconstruction outcomes 21 . However, at present, the positioning of the bone tunnel for PCL reconstruction, under arthroscopic surgery, mainly depends on direct vision and intraoperative imaging positioning during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of arthroscopic techniques, PCL reconstruction is becoming a common treatment strategy for PCL injuries. Precise anatomical positioning of the graft tunnel is essential for obtaining good PCL reconstruction outcomes 21 . However, at present, the positioning of the bone tunnel for PCL reconstruction, under arthroscopic surgery, mainly depends on direct vision and intraoperative imaging positioning during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those in two recent studies, who reported the postoperative outcomes of the distal tibial tunnel in PCL reconstruction. 20,41 Lin et al 20 included 15 patients who underwent PCL reconstruction using distal tibial tunnel. They found that a distal tunnel significantly reduced the killer turn, but the clinical outcome was similar with that of anatomic tibial tunnel within a mean follow-up of 35.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a distal tunnel significantly reduced the killer turn, but the clinical outcome was similar with that of anatomic tibial tunnel within a mean follow-up of 35.4 months. Yoon et al 41 retrospectively reviewed the clinical and radiologic outcomes of patients undergoing PCL reconstruction with anatomic and low tibial tunnels. The findings showed similar clinical and radiologic outcomes between anatomic and distal tibial tunnel at 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 6 However, efforts have kept been made to preserve the remnant during PCL reconstruction with the expectation of better surgical results. 7 , 8 , 9 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%